Mineralogy of Tailings Dump around Selebi Phikwe Nickel-Copper Plant, Botswana - G Ekosse; D J van Den Heever; L de Jager; O Totolo (Journal of Applied Sciences and Environmental Management, 2005)
This study aimed at mineralogically characterizing the tailings dump emanating from the mining and smelting of nickel-copper (Ni-Cu) at Selebi Phikwe, Botswana, Southern Africa. Samples of tailings dump around the Selebi Phikwe Ni-Cu plant were studied using petrographic microscopy and X-ray Powder Diffraction (XRPD) technique. The tailings dump comprised of the following minerals: nickelblodite, pyrrhotite, quartz, pentlandite, malachite, chalcopyrite, actinolite, cristobalite, tremolite, kaolinite, mica and albite. Nickelblodite and malachite were mineralized from the primary ore minerals in the tailings dump. The sulfur-rich minerals contained in the tailings dump serve as principal promoting sources for acid mine drainage in the immediate surrounding environment. Consequently, aspects of pollution management such as phytoremediation and phytomining, and environmental desulfurization could be introduced as pollution control measures at Selebi Phikwe.